Effect of Vitamins A, C, and E Supplementation in the Treatment of Metabolic Syndrome in Albino Rats - L. S. Bilbis; S. A. Muhammad; Y. Saidu; Y. Adamu (Biochemistry Research International)
Obesity and metabolic syndrome increase the risk of cardiovascular morbidity and mortality. Oxidative stress seems to be involved in the path physiology of cardiovascular complications of metabolic syndrome. In this study we investigated the effects of vitamins A, C, and E in the management of metabolic syndrome traits condition in albino rats fed with high salt diet. The rats were placed on 8% NaCl diet for 5 weeks and then supplemented with these vitamins for additional 4 weeks in the presence of salt diet. Supplementation with vitamins significantly (P<0.01 ) decreased blood pressure of the rats as compared with the control. Supplementation also significantly (P<0.05) reduced serum total cholesterol, triglyceride, low-density lipoprotein cholesterol, and very-low-density lipoprotein cholesterol and increased high-density lipoprotein cholesterol, and total antioxidant status as compared with untreated group. The percentage protection of the supplemented groups against atherogenesis indicated 55.50±3.75%. Percentage weight gain indicated significant positive correlation with triglyceride, insulin resistance, and malondialdehyde while total antioxidant status and nitric oxide showed significant negative correlation. Salt diet significantly (P<0.05) induced features of metabolic syndrome. The result, therefore, indicated strong relationship between obesity and metabolic syndrome and underscores the role of these vitamins in the management of metabolic syndrome.